The Influence of Supply Chain Management and Organization Performance toward Turnover Intention at the Head Office of PT Bank Syariah Mandiri - Emeraldo Zahari, Amiral; Supriyati, Yetti; Santoso, Budi (ExcelingTech, 2020)
Abstract-Human resources is one of the crucial aspects to achieve the company goals which can be handle by supply chain strategy. The relationship among supply chain strategy, management of core operational functions and improvement in performance requires better understanding. In banks, turnover intention is the process or attitude of an employee to consider leaving the current job, and to find alternative employment opportunities in other organizations or companies that are better. The objective of this research was to find out the influence of Supply Chain Management and Organization Performance toward Turnover Intention at the Head Office of PT Bank Syariah Mandiri. In this research, the researcher took the samples by using non-probability sampling method with a purposive sampling technique. The samples were the permanent officers of PT. Bank Syariah Mandiri (Head Office) consisted of 291 respondents from the total of 404 permanent officers. The researcher used structural equation model in testing, analyzing the data, and model development. The Data were analyzed by using statistical software tools (LISREL 8.8). The paper seeks to establish and validate a theoretical model linking the supply chain strategy, core operational functions and organizational performance in bank. The data validates the theoretical basis of the constructs and shows supply chain strategy has an overall positive impact on multiple performance dimensions through strategically aligned core operational functions.